2019
DOI: 10.1088/1755-1315/309/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Protein Cocoa Beans as Food Bioactive Precursor to Prevent Hypertension

Abstract: Cocoa beans are superior plantation commodity in Indonesia. The fermentation practice on cocoa beans process has a very important role not only to produce quality seeds but also bioactive peptides. Proteolysis that occurs during cocoa fermentation can produce peptide fragments that have health benefits, such as antihypertension. Hypertension is a major risk factor for cardiovascular diseases and has an important impact on public health. Scientific research gathered strong evidence about the role of cocoa beans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…After polyphenols, proteins undergo the most intensive changes during the fermentation of cocoa beans (Haliza et al ., 2019). This hydrolysis has been mainly attributed to proteolytic endogenous enzymes within the cotyledon, such as endopeptidases and carboxypeptidases, which are activated during the changes in temperature and pH caused by microbial fermentation by‐products ( e.g .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After polyphenols, proteins undergo the most intensive changes during the fermentation of cocoa beans (Haliza et al ., 2019). This hydrolysis has been mainly attributed to proteolytic endogenous enzymes within the cotyledon, such as endopeptidases and carboxypeptidases, which are activated during the changes in temperature and pH caused by microbial fermentation by‐products ( e.g .…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it has been widely reported that peptide sequences with branched and hydrophobic amino acid residues in the C‐terminal such as isoleucine, alanine, methionine, valine, phenylalanine, tyrosine and tryptophan are highly related to ACE inhibition. Meanwhile, other studies have suggested that peptide sequences with valine, leucine, glycine and isoleucine in the N‐terminal may also enhance ACE inhibition (Haliza et al ., 2019; Álvarez‐Olguín et al ., 2023). Henceforth, in the present study ACE inhibition activity may be related to peptides with these amino acids in their sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Two major events occur during fermentation: Firstly, microbial action on the mucilaginous pulp produces alcohols and acids as well as heat. Secondly, micro-organisms produce metabolites that diffuse into cotyledons and trigger complex biochemical reactions [5,2,6].…”
Section: Introductionmentioning
confidence: 99%